Synthesis of Nitrogen-Doped Carbon Nanotubes Using Injection-Vertical Chemical Vapor Deposition: Effects of Synthesis Parameters on the Nitrogen Content. (16th December 2015) - Hachimi, Abdouelilah; Merzougui, Belabbes; Hakeem, Abbas; Laoui, Tahar; Swain, Greg M.; Chang, Qiaowan; Shao, Minhua; Atieh, Muataz Ali
Abstract : Nitrogen-doped CNTs (N-CNTs) were synthesized using an injection-vertical chemical vapor deposition (IV-CVD) reactor. This type of reactor is quite useful for the continuous mass production of CNTs. In this work, the optimum deposition conditions for maximizing the incorporation of nitrogen were identified. Ferrocene served as the source of the Fe catalyst and was dissolved in acetonitrile, which served as both the hydrocarbon and nitrogen sources. Different concentrations of ferrocene in acetonitrile were introduced into the top of a vertically aligned reactor at a constant flow rate with hydrogen serving as the carrier. The effects of hydrogen flow rate, growth temperature, and catalyst loading (Fe from the ferrocene) on the microstructure, elemental composition, and yield of N-CNTs were investigated. The N-CNTs possessed a bamboo-like microstructure with a nitrogen doping level as high as 14 at.% when using 2.5 to 5 mg/mL of the ferrocene/acetonitrile mixture at 800°C under a 1000 sccm flow of hydrogen. A production rate of 100 mg/h was achieved under the optimized synthesis conditions.